2021
DOI: 10.1155/2021/5519709
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Review on the Effects of Laser Photobiomodulation on Skeletal Muscle Fatigue in Spastic Patients

Abstract: Peripheral muscle fatigue is a common experience in daily life. Every individual at some point in their life has realized the inability to maintain muscle contraction, a phenomenon known as fatigue. Interestingly, neurological patients with peripheral sequelae such as spastic muscle contraction are able to remain in a pattern of muscle contraction for prolonged periods. The effects of laser therapy are already recognized in muscle contraction to delay skeletal muscle fatigue, prolong physical activity, and red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 127 publications
(179 reference statements)
0
3
0
Order By: Relevance
“…The efficacy of PBMT as a non-invasive pain reduction approach has been shown in several studies. [82][83][84][85] The analgesic effect of PBMT might be a result of its positive impact on the reduction of muscle spasms, 86 a decrease of inflammation by attenuating the levels of PGE2 87 and inhibiting COX-2, 88 an increase in nociceptive threshold, 83 enhancing the peripheral endogenous opioid production, 89 and suppression of nerve conduction in myelinated Aδ and unmyelinated C fibers. 90 One of the unique advantages of the PBMT analgesic effect is that no development of tolerance or adaptation to the PBMT has been reported so far.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of PBMT as a non-invasive pain reduction approach has been shown in several studies. [82][83][84][85] The analgesic effect of PBMT might be a result of its positive impact on the reduction of muscle spasms, 86 a decrease of inflammation by attenuating the levels of PGE2 87 and inhibiting COX-2, 88 an increase in nociceptive threshold, 83 enhancing the peripheral endogenous opioid production, 89 and suppression of nerve conduction in myelinated Aδ and unmyelinated C fibers. 90 One of the unique advantages of the PBMT analgesic effect is that no development of tolerance or adaptation to the PBMT has been reported so far.…”
Section: Discussionmentioning
confidence: 99%
“…Observed improvements in general patient health from PBM include enhanced mobility 36,37 ; reduced muscle fatigue and cramping 38,39 ; reduced pain and inflammation 40,41,42 ; improved breathing with reduced bronchoconstriction 43 ; improved cardiovascular performance 44 ; amelioration of digestive distress 45,46,47,48 ; accelerated wound healing 49,50,51 ; reduced mental stress 52,53 ; improved sleep quality 54 , enhanced brain waste removal 55 ; and an heightened sense of overall wellbeing. Although the enumerated PBM indications extend beyond acute COVID etiology, as a multisystem inflammatory disease long COVID involves all of the aforementioned mechanisms.…”
Section: Why Pbm and Why Now?mentioning
confidence: 99%
“…According to Stamborowski et al (2021), photo bio-stimulation, in other words, LLLT, can be effective in the treatment of multiple musculoskeletal conditions while Putri et al (2020) suggested LLLT can be beneficial in reducing spasticity in CP children.…”
Section: Introductionmentioning
confidence: 99%